Optimalisasi Partisipasi Aktif Peserta Didik melalui Wordwall dalam Model Problem Based Learning pada Pembelajaran Pendidikan Pancasila Kelas VII SMP Negeri 4 Kota Madiun - Anissa Wika Alzana (STKIP Subang, 2026)
This study aims to describe efforts to optimize students' active participation through the use of Wordwall-based interactive learning media integrated into the Problem-Based Learning (PBL) model in Pancasila Education learning for seventh-grade students at SMP Negeri 4 Kota Madiun. This study employed a Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, conducted in three cycles consisting of planning, action, observation, and reflection. Data were collected through observations, documentation, field notes, and learning reflections and were analyzed qualitatively. The findings indicate that the integration of Wordwall into the PBL model gradually enhanced students' active participation, as evidenced by increased confidence in asking questions and expressing opinions, greater involvement in group discussions, improved learning focus, and enhanced collaboration skills. The learning process became more interactive, engaging, and student-centered.